1987
DOI: 10.1071/sr9870055
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride interactions with hydrous aluminum oxides and alumina

Abstract: Fluoride ion interaction with amorphous Al(OH),, gibbsite or alumina (Al2O3) has been investigated over a range of pH values (3-8) and F- concentrations (0.1-1 mM) . At pH <6 and total F- : Al ratios >2.5, most of the amorphous AI(OH)3 gel dissolved through formation of AlF, complexes, with the distribution of fluoro ions being determined by the equilibrium F- value. At lower F : Al ratios, some solid persisted in the pH 4-7 region and strongly sorbed F- from solution. Maximum uptake occurred in the pH 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 0 publications
2
42
0
Order By: Relevance
“…However, less stringent limits for effluent that is not to be released in sensitive locations are readily reached. For example in New South Wales a fluoride concentration of 20 mg/L is the maximum concentration permissible before the waste becomes a controlled liquid waste requiring a licence for transport and disposal (EPA, 1999 Farrah et al (1987) investigated the interaction of fluoride ion with amorphous aluminium hydroxide (Al(OH) 3 ), gibbsite (naturally occurring aluminium hydroxide) and aluminium oxide (Al 2 O 3 ) over a range of pH values from 3 to 8 and F À concentrations from 0.1-1 mM (w1.9-19 mg/L). At pH < 6 and total F:Al ratios >2.5, most of the amorphous Al(OH) 3 gel dissolved through formation of Al-F, complexes, with the distribution of fluorine being determined by the equilibrium F À value.…”
Section: Adsorption Techniquementioning
confidence: 99%
“…However, less stringent limits for effluent that is not to be released in sensitive locations are readily reached. For example in New South Wales a fluoride concentration of 20 mg/L is the maximum concentration permissible before the waste becomes a controlled liquid waste requiring a licence for transport and disposal (EPA, 1999 Farrah et al (1987) investigated the interaction of fluoride ion with amorphous aluminium hydroxide (Al(OH) 3 ), gibbsite (naturally occurring aluminium hydroxide) and aluminium oxide (Al 2 O 3 ) over a range of pH values from 3 to 8 and F À concentrations from 0.1-1 mM (w1.9-19 mg/L). At pH < 6 and total F:Al ratios >2.5, most of the amorphous Al(OH) 3 gel dissolved through formation of Al-F, complexes, with the distribution of fluorine being determined by the equilibrium F À value.…”
Section: Adsorption Techniquementioning
confidence: 99%
“…8d showed that, at the equilibrium pH of the defluoridation system (pH = 6.4-6.6), three different species of aluminium fluoride were feasible (AlF 4 À AlF 5 2À and AlF 6 3À ) in the system. The F À interaction with different species of aluminium rich materials have been studied [35][36][37][38] and it has been reported that the maximum uptake of F À occur in the pH range of 5.5-6.5 [39]. At lower pH, fluoride uptake decreased due to the tendency of Al 3+ to dissolve and form positively charged AlF complexes (AlF 2+ , AlF 2 + ) which are repelled by the positively charged surfaces of Al oxides at these conditions (because the PZC of Al oxides > pH 7) [36].…”
Section: Initial Solution Phmentioning
confidence: 99%
“…Phosphate and sulphate (inner-sphere forming species) have been shown to have negative effects on the loading capacity of fluoride, while outer-sphere forming species (chloride and nitrate) improved fluoride removal slightly [22]. At pH values less than 3.7, fluoride removal generally decreases due to the formation of AlF x soluble species, while in alkaline solutions OH À displaced F À [31]. A study by Cengeloglu et al [24] investigated the adsorption capacity of untreated and hydrochloric treated red mud.…”
Section: Introductionmentioning
confidence: 98%